Changes in lower limb kinematics coordination during 2000m ergometer rowing among male junior national rowers - Zainuddin, F. L.; Zahiran, A.; Umar, M. A.; Shaharudin, S.; Razman, R. M. (Journal of Physical Education and Sport, 2019)
Joint coordination is important for rowers because a non-optimal strategy may limit the power output and movement efficiency during rowing. Although lower limb joint coordination is fundamental during rowing, studies on this aspect, particularly during ergometer rowing, are scarce. The purpose of this study was to evaluate the changes of lower limb kinematics coordination during a 2000m timetrial on a dynamic rowing ergometer. Ten male junior national rowers were recruited. Three-dimensional lower limb kinematics were captured and recorded for ten strokes for every 500m splits of 2000m time trial using nine high-speed infrared cameras. Then, Principal Component Analysis (PCA) was applied to determine the coordination coefficients that represented the temporal activity of the coordination and coordination vectors corresponding to the relative weightings of each kinematic variable within the coordination. The rowers completed 2000m timetrial in 7.57 ± 0.42 minutes. To the best of our knowledge, this was the first study that evaluated joint coordination during 500m splits of 2000m rowing time trial among trained rowers. Joint coordination of lower limb kinematics could be distinguished in two robust factors that were consistent across 500m splits of 2000m rowing time trial. Main coordination was contributed by hip joint in all planes, knee joint in the sagittal and frontal planes, and ankle joint in the sagittal and transverse planes. Meanwhile, minor coordination was comprised of knee joint in the transverse plane and ankle joint in the frontal plane.There were small changes in the loading vectors for both factors across the time trial. Coaches and rowers may emphasize their training on the specific joint movement that contributes to the main coordination. This strategy may enhance their rowing performance and joint coordination.